2017
DOI: 10.1002/slct.201702134
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Friendly Alkali‐Free Arginine‐Assisted Hydrothermal Synthesis of Different Layered Double Hydroxides and Their Chromate Adsorption/Reduction Efficiency

Abstract: A new one‐pot synthesis of highly crystalline MgAl‐, CoAl‐ and ZnAl‐layered double hydroxides (LDHs) containing NO3− as interlayer anion along with the surface functionalization of L‐arginine was demonstrated by the ecofriendly alkali‐free arginine‐assisted hydrothermal method to examine the adsorptive reduction of chromate (CrO42−) from aqueous solutions. The amino acid mediated water hydrolysis resulted abundant OH− in the medium, which served as precipitant, and the NO3− from metal precursor acts as an inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…The high resolution of N 1s can be resolved into three different peaks at 400.7 eV, 399.4 eV and 398.1 eV (Figure C), which were assigned to the protonated amine (‐NH + ), the undoped amine‐like nitrogen atoms (‐NH‐) and the imine‐like (‐N≡) groups, respectively ,. Cr(VI) adsorption process, the proportion of ‐NH + sharply decreased from 44% to 31%, and ‐NH‐ decreased from 56% to 52% (Table ), which confirmed the redox reaction between ‐NH + and ‐NH‐ in PANI/AlOOH and Cr(VI) . The high resolution of N 1s spectra further confirmed that the amine group was in Cr(VI) removal process.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…The high resolution of N 1s can be resolved into three different peaks at 400.7 eV, 399.4 eV and 398.1 eV (Figure C), which were assigned to the protonated amine (‐NH + ), the undoped amine‐like nitrogen atoms (‐NH‐) and the imine‐like (‐N≡) groups, respectively ,. Cr(VI) adsorption process, the proportion of ‐NH + sharply decreased from 44% to 31%, and ‐NH‐ decreased from 56% to 52% (Table ), which confirmed the redox reaction between ‐NH + and ‐NH‐ in PANI/AlOOH and Cr(VI) . The high resolution of N 1s spectra further confirmed that the amine group was in Cr(VI) removal process.…”
Section: Resultsmentioning
confidence: 55%
“…Of course, XPS analysis only provided the surface information rather than bulk concentration. Compare with PANI, more Cr(VI) was reducing to Cr(III) on PANI/AlOOH, indicating the enhanced Cr(VI) reduction ability of PANI/AlOOH . The appearance of Cr(III) species could be clearly confirmed by high resolution O 1s spectra in Figure A.…”
Section: Resultsmentioning
confidence: 78%
“…The image in Figure 2a shows a small hexagonal platelet of Zn/Al LDH material, while the image in Figure 2b shows a large hexagonal platelet. The size of hexagonal platelet of Zn/Al LDH was large as increasing in the molar ratio of Zn 2+ / Al 3+ because of more ZnO phase and ZnAl2O4 spinel were present [6]. The information about the type of bonds formed by the anions and their orientations of Zn/Al LDH material was obtained by FTIR analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Research on synthesis of Zn/Al LDH via this method, where zinc nitrate solution and aluminum nitrate solution are representing as a divalent cation (M II ) and a trivalent cation (M III ) respectively, are mixed with the addition of ammonium carbonate solution under constant pH [4], [5]. The mixing of both divalent and trivalent cations can cause the electrostatic interaction between the positive and negative interlayer because of the anion exchange capacity affected by the molar ratio [6]. The studies on the different molar ratios of Zn/Al LDH can lead to changes in its structure and properties.…”
Section: -X M Iiimentioning
confidence: 99%
“…The wide-scan XPS spectrum of La-BC after experiments showed that the peak of Cr element has appeared in La-BC (900℃) (Figure 8a). Moreover, the corresponding peaks where the binding capacity was 577.8 eV, 579.7 eV proved that Cr(VI) were successfully absorbed (Figure 8b) [42]. Cr has been absorbed successfully, In the La3d images, the binding energy of element La had negative displacement (0.4-0.7eV) after adsorption (Figure 8c), indicating that electron transfer occurred between La-BC (900 ℃ ) and chromite, which formed a strong chemical bond [30].…”
Section: Adsorption Mechanismmentioning
confidence: 92%